IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH LISTENING TEAM LEARNING STRATEGIES IN CIVICS LEARNING AT GRADE V SD NEGERI 184 PEKANBARU - Daniel Abed Nego; Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study was initiated by the students’ low achievement in Civics learning at grade class V SD Negeri 184 Pekanbaru. The studets’ average score before using listening team learning strategy was 69.73; as a result, it did not reach the specified Minimum Completeness Criteria which was 75. For this reason, teachers needed to improve the learning process; one of which was using listening team learning strategy. This strategy began with the presentation of the material by the teacher, then continued by dividing students into several small groups consisting of four people. Each group member performed the role of a questioner, answerer, buffer, and conclusion drawer. Then, the activitiy ended with concluding the learning material. The purpose of this study was to improve students’ learning outcomes in Civics at grade V SD Negeri 184 Pekanbaru. This study was conducted in 2 cycles. The data were obtained from teacher and student activity as well as students’ learning outcome on daily tests in each cycle. It was found that the teacher’s activity increased in cycle I from 41.66% (very low) to 58.33% (less). Then, in cycle II, it increased from 66.66% (enough) to 91.66% (very good). This also occurred at student activities with the percentage in the first cycle was from 50% (very poor) to 58.33% (less) and it increased the second cycle from 75% (enough) to 83.33% (good). In addition, the students’ learning outcomes in civics subject also increased from the average base score of 69.73 to 75.68 in the first cycle (8.53%). In the second cycle, it increased by 20.15% from the basic score to 83.78. Thus, the listening team learning strategy improved the students’ learning outcomes in Civics learning at grade V SD Negeri 184 Pekanbaru.